TWO TAURODONT PRIMARY MOLARS WITH PULPAL INVOLVEMENT: A MANAGEMENT APPROACH - .Shijee M; Ponnudurai Arangannal; Jeevarathan; .Janani Vinodhini; Madhumitha; Ramya Chellamal; .Ishwarya Dhevi G R (The Bioscan, 2024)
Taurodontism is basically a developmental disorder with large pulp chambers and furcal areas located closer to the apex. The prevalence of taurodontism is very less i.e 0.54% in primary dentition. The main problem faced in endodontic management of a taurodont tooth is the short roots which makes instrumentation almost difficult or not possible at all.So, certain modifications had to be made in pulpal therapy of a taurodont primary tooth considering the morphological changes of the tooth.This paper discusses the management of two pulpally involved taurodont primary molars in a 4.5 year old patient.